Integration of 3D animation flipbook to enhance spatial visualization in molecular geometry learning - Saputra, Dikky Hutama; Dwiningsih, Kusumawati (Indonesian Journal of Educational Development (IJED), 2025)
Students’ limited spatial visualization skills pose challenges in understanding abstract chemical concepts such as molecular geometry. This study aimed to develop an interactive flipbook assisted by 3D animations to enhance students’ spatial visualization and comprehension of molecular geometry. This research employed a Research and Development (R&D) approach using the ADDIE model and involved 32 purposively selected eleventh-grade students at SMA Negeri 7 Surabaya. Data were collected using validation sheets, student response questionnaires, pre-test and post-tests, and observation sheets, with instrument reliability confirmed by expert judgment and Cronbach’s Alpha. Validation results showed that the flipbook was highly valid in both content and construct. Students’ responses indicated a high level of practicality (92.9%). Effectiveness testing revealed significant improvement in learning outcomes, with an average N-Gain of 0.75 for competence and 0.80 for spatial ability, both categorized as high. These results suggest that the 3D-assisted flipbook enables students to visualize and manipulate molecular structures, thereby reducing reliance on imagination and strengthening conceptual understanding. Teachers are recommended to adopt 3D-assisted flipbooks as a low-cost and effective instructional medium to foster students’ spatial reasoning and improve chemistry learning outcomes.